Stromal vascular fraction therapy for knee osteoarthritis: a systematic review - Anna Boada-Pladellorens; Mercè Avellanet; Esther Pages-Bolibar; Anna Veiga (Therapeutic Advances in Musculoskeletal Disease, 2022)
Background: Regenerative cell therapies, such as adipose-derived stromal vascular fraction (SVF), have been postulated as potential treatments for knee osteoarthritis (KOA). Objectives: To assess the efficacy and safety of SVF treatment against placebo and other standard therapies for treating KOA in adult patients. Design: A systematic review. Data sources and methods: We searched the following databases: MEDLINE via PubMed, Epistemonikos, PEDro, DynaMed, TripDatabase, Elsevier via Clinicalkey and Cochrane Controlled Trials Register. We included prospective interventional studies where treatment with SVF in adults with KOA was compared against placebo or other standard therapies, and results were objectively measured with at least one widely recognised osteoarthritis scale. Results: Among 266 studies published until May 2021, nine met our inclusion criteria. A total of 239 patients (274 knees) were included in our study. The follow-up ranged from 6 to 24 months. Six studies had a control group (only one being placebo). All studies showed that SVF improved pain and functionality measured, in most cases, with the visual analogue scale and the Western Ontario and McMaster Universities Osteoarthritis Index. In addition, five studies reported an improvement in anatomical structures, as detected in MR images. However, the number of cells contained in SVF varied substantially between different studies, which could induce a comparison bias. Conclusion: Although based on a small number of dissimilar studies, SVF was considered a safe treatment for KOA and could be promising in terms of pain, functionality and anatomical structure improvement. However, SVF products need to be standardised, the number of cells homogenised and the use of concomitant treatments reduced to establish proper comparisons. Registration: PROSPERO registration number: CRD42021284187.